The Weight of Fear of Violence in Household Budgets - Truzzi, Bruno (Criminal justice review, 2021)
This article investigates the relationship between the perception of violence and the spending on security goods and services in households. Individual microdata from a random national survey on family budget carried out in Brazil in 2008-2009 were used for modeling the household spending using two instrumental variables. The stability of results was checked by applying the Lasso-Gaussian regularization method in the selection of the statistically significant variables. Positive relationships were found between household spending on security goods and services and (i) the fear of insecurity at the household level, (ii) the neighbors’ spending on security, and (iii) the registered criminality, but no evidence was found on the relationship between the role of police on household spending on security goods and services.